HATE SPEECH ON SOCIAL MEDIA: A CASE STUDY OF BLASPHEMY IN INDONESIAN CONTEXT - Rotua Elfrida; Arsen Nahum Pasaribu (English Review: Journal of English Education, 2023)
Many scholars have conducted research on hate speech, spanning from hate speech delivery tactics to the negative consequences they create, as well as the role of technology in the dissemination of hate speech on social media. However, research on hate speech categories and degrees is still relatively unexplored. As a result, the purpose of this research is to uncover the strategies and levels of hate speech on social media, primarily YouTube channels, in response to the Minister of Religion's comments about the sound of mosque loudspeakers that need to be adjusted in volume. This comment has generated both positive and negative reactions in Indonesian society. This research looks into netizen comments in the comments column on the YouTube channel that carries the statement. Purposive sampling was used to select 300 comments from among the 840 comments in the comments column. For the purposes of this study, the sample was obtained in the form of comments containing hate speech. The data was then analyzed using content analysis, in which the data was categorized and categorized according to hate speech categories. According to the study's findings, there are three types of hate speech in netizen comments: early warning, dehumanization and demonization, and violence and incitement. Early warning is the most common type of hate speech, followed by violence and hostility, as well as dehumanization and demonization. Due to cultural influences and contrasts in rank and power between the commentator and the person who is the subject of the hate speech, hate speech delivered by Indonesian netizens tends to be dominated by disagreement, negative character, and action.